Endothelin‐1 gene polymorphism in sudden sensorineural hearing loss. (5th August 2013) - Uchida, Yasue; Teranishi, Masaaki; Nishio, Naoki; Sugiura, Saiko; Hiramatsu, Mariko; Suzuki, Hidenori; Kato, Ken; Otake, Hironao; Yoshida, Tadao; Tagaya, Mitsuhiko; Suzuki, Hirokazu; Sone, Michihiko; et al.
Abstract : Objectives/Hypothesis: Endothelin‐1 is a potent vasoconstrictor peptide that is widely distributed throughout the mammalian body including the spiral modiolar artery, vestibule, and cochlea. This study aimed to investigate the association between the Lys198Asn (G/T) polymorphism (rs5370) of the endothelin‐1 gene and sudden sensorineural hearing loss (SSNHL). Study Design: Case‐control study. Methods: Seventy‐two SSNHL patients (mean age, 58.3 ± 14.0 years) were compared with 2, 159 controls included in a community‐based study of aging. Multiple logistic regression was used to obtain odds ratios (ORs) for SSNHL. In subgroup analysis, patients with SSNHL who visited to the hospital within the first month of onset were selected to assess audiometric features according to genotype. Pure‐tone averages at 250, 500, 1, 000, 2, 000, and 4, 000 Hz were calculated in the affected ear. Results: Under the recessive genetic model, after adjustment for age, sex, histories of hypertension, dyslipidemia and diabetes, the crude and adjusted ORs for SSNHL risk were 2.209 (95% confidence interval [CI]: 1.140‐4.281) and 2.173 (95% CI: 1.086‐4.348), respectively. No significant ORs were observed under the additive and dominant models. The severity of SSNHL differed significantly between genotypes. The mean pure‐tone averages at the initial visit were 78.6, 66.4, and 57.8 dB for the GG, GT, and TT genotypes, respectively ( P = .034). Conclusions: Our study indicates that the recessive genotype was significantly associated with increased SSNHL risk; however, the severity was lower in these individuals than it was in those with the wild‐type genotype. Endothelin‐1 may be implicated in SSNHL. Level of Evidence: 3b Laryngoscope, 123:E59–E65, 2013